2020
DOI: 10.1039/d0ra08039j
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the mechanism of CO2 capture and separation by porous liquids

Abstract: A POC-type porous liquid has the ability to absorb CO2 and the cage provides a cavity for absorption. The dominant interaction between CO2 and the cage is π–π interaction. The optimal capacities of the three porous organic cages are 4, 2 and 4 eq.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…It reveals the basic chemistry that makes up covalent structures and provides a rich representation of van der Waals interactions, hydrogen bonding, and spatial repulsion in small molecules, molecular complexes, and solids. Red indicates strong attractive interactions (e.g., hydrogen bonding and strong electrostatic interactions), transition regions indicate typical van der Waals interactions, and blue represents strong non-bonding overlap [49]. As in Figures 8 and S6, the typical van der Waals interaction in green between the pristine h-BN and THs is the π-π interaction.…”
Section: Speciesmentioning
confidence: 95%
“…It reveals the basic chemistry that makes up covalent structures and provides a rich representation of van der Waals interactions, hydrogen bonding, and spatial repulsion in small molecules, molecular complexes, and solids. Red indicates strong attractive interactions (e.g., hydrogen bonding and strong electrostatic interactions), transition regions indicate typical van der Waals interactions, and blue represents strong non-bonding overlap [49]. As in Figures 8 and S6, the typical van der Waals interaction in green between the pristine h-BN and THs is the π-π interaction.…”
Section: Speciesmentioning
confidence: 95%
“… 41 However, the molecular nature of POCs in type II porous liquids does not allow for the periodic description by slab models; instead, studies either model POC-based porous liquids via bulk simulations, 26 or use single cage models to ascertain individual interactions between solvent/gas molecules and the cage. 67 Model selection is a function of both the chemical composition ( i.e. extended framework vs. molecular material) and the feature(s) of interest.…”
Section: Characterisation Of Porous Liquidsmentioning
confidence: 99%
“…Yet, the increased computational expense of DFT necessitates smaller models, typically composed of two to three porous liquid components. For example, binding energies are calculated to examine specic molecular interactions, including those between the gas/porous motif, 67,76 gas/solvent and gas/porous liquid, 77,78 and solvent/porous motif. 67,79 Beyond binding energies, exchange energies of CO 2 /CHCl 3 in a series of POCs provided a detailed picture of CO 2 separation by type II porous liquids.…”
Section: Computational Characterisationmentioning
confidence: 99%
“…Porous liquids with crown ether substituted cages dissolved in 15‐crown‐5 solvent were also studied using MD simulations for different cage to solvent ratio to understand the effect of solvent on gas adsorption and separation of mixture of either CO 2 /N 2 or CO 2 /CH 4 gases [25] . Porous covalent organic cages, and tetrahedral coordination cages based porous ionic liquids have also been developed [26–28] . It has also been shown that bulky ionic liquids with different applications in energy storage device, [29] CO 2 capture, [30] toluene capture, [31] and lubrication [32] can be employed as green solvent [33,34] for the fabrication of porous liquids.…”
Section: Introductionmentioning
confidence: 99%